Wolfhart Pannenberg bied "n weerwoord teen die ontwaarding van die geskiedenis - Botes, H. J. (HTS teologiese studies, 2001)
Wolfhart Pannenberg's thoughts as answer against the devaluation of history. In this day and age, nobody any longer believes in the redemptive essence of history (Lyotard). One result of modernism is that humankind is left without history, due to a number of factors. Thus, history as such, and more specifically, church history as theological discipline, finds itself in a crisis. Yet, despite criticism that can be levelled against Pannenberg's thinking, his theory, nevertheless, serves as an answer against the devaluation of history. Given that, the Person ofthe Risen Lord as head of the church has, unquestionably, throughout the ages occupied a central position in both the history of the church and that of the world, Pannenberg's consideration of Chist's resurrecion, in particular, may stand the church in good stead.